Aging Process in Dermal Fibroblast Cell Culture of Green Turtle (Chelonia mydas) - Anggraini Barlian; Yemima D Riani (3BIO: Journal of Biological Science, Technology and Management, 2020)
Senescence in green turtle is an interesting process to study because until now no clear explanation has been established about senescence at cellular or molecular level in this species. One of common markers used for detecting senescence is telomere shortening. Reduced telomerase activity may also cause senescence. The aims of this research are to establish and identify dermal fibroblast cell culture from green turtle and also to compare telomere length and telomerase activity from the cells subculture 5 and 14. Cells were identified with Rabbit Anti-Vimentin Polyclonal Antibody and Goat Polyclonal Antibody using confocal microscope. Telomere length was obtained using TeloTAGGG Telomere Length Assay (Roche), while telomerase activity was obtained using TeloTAGGG Telomerase PCR ElisaPlus. Primary cell culture from green turtle skin showed fibroblastic morphology and immunocytochemistry results using vimentin antibody proved that the culture was fibroblast cell. Measurement of telomere length and telomerase activity showed that telomere length and telomerase activity of subculture 14 was greater than subculture 5. However, based on morphology, green turtle fibroblast skin cell culture showed senescent morphology. Therefore, possible aging mechanism that the green turtle fibroblast skin cell culture underwent did not go through both telomere shortening and reduced telomerase activity.